Foam gel-casting preparation of SiC bonded ZrB2 porous ceramics for high-performance thermal insulation - Zhang, Xin; He, Jiangfeng; Han, Lei; Huang, Zhong; Xu, Ke; Cai, Weijie; Wu, Shuaibing; Jia, Quanli; Zhang, Haijun; Zhang, Shaowei (Journal of the European Ceramic Society, 2023)
Lightweight SiC-ZrB2 porous ceramics is of great potential as thermal insulation material used in aerospace, chemical and energy industries. In this work, a series of SiC bonded ZrB2 (SiCb-ZrB2) porous ceramics with porosity high up to 86.9% were prepared by a simple foam gel-casting method. The SiCb-ZrB2 porous ceramic prepared at 1573 K exhibited a low thermal conductivity of 0.280 W/(m∙K) and a reasonable compressive strength of 0.52 MPa. It could maintain the original geometric shape and microstructure after a secondary heat treatment at 1473 K in inert atmosphere. When heating the samples with thickness of 30 mm for 12 min with an alcohol spray lamp (∼1273 K), the temperatures of the cold sides of SiCb-ZrB2 ceramics were all lower than 432 K, demonstrating their exceptional insulation capabilities. The present work provides a simple route to produce robust and thermally-insulating non-oxide porous ceramics for use under high temperature.